The Impact of Health Education on High-Risk Pregnant Women's Knowledge of Preventing Pregnancy Complications in the Bukit Mulya Community Health Center Mukomuko Regency 2025 - Dewi Suparti; Nimas Ayu Lestari; Bella Anarkie (Student Scientific Journal, 2026)
In 2020, an estimated 287,000 maternal deaths occurred, equivalent to one death every two minutes. A recent WHO study reported that hemorrhage, most often occurring during or after childbirth, was responsible for nearly a third (27%) of maternal deaths, with preeclampsia and other hypertensive disorders contributing an additional 16%. The purpose of this study was to determine the effect of health education on the knowledge of high-risk pregnant women regarding the prevention of pregnancy complications in the Bukit Mulya Community Health Center (Puskesmas) working area in Mukomuko Regency. This study used a quasi-experimental "one-group pretest-posttest" design, involving only one group without a control group. The pretest was administered to each respondent before the treatment. The researcher then administered the treatment to each respondent, and then administered the posttest to 33 respondents using a total sampling technique. Univariate analysis revealed that more than half of the respondents 19 (57.6%) in the Bukit Mulya Community Health Center working area in Mukomuko Regency) had poor knowledge before receiving health education, while more than half 17 (51.5%) had good knowledge after receiving health education. The bivariate analysis results, due to the data being normally distributed, yielded a paired samples test with a p-value of 0.000 < 0.05. Therefore, Ho is rejected and Ha is accepted, indicating a significant effect between health education and the knowledge of high-risk pregnant women regarding preventing pregnancy complications. This is to ensure that health workers can improve and maintain the provision of planned and continuous health education to high-risk pregnant women using engaging and easy-to-understand methods and media.